A simple solution to help with feeding difficulties in neonates with cleft palate: A case report - Lucky Yadav; Navraj Mattu; Pravesh Mehra; Diwakar Vasisth (Journal of Family Medicine and Primary Care, 2024)
Feeding a neonate baby with a complete cleft lip and palate is a problematic pursuit because of the communication between the oral and the nasal cavity and associated problems. This present case is of a 6-day-old underweight neonate with feeding difficulties due to the cleft palate. In this case report, simple, uncomplicated steps for the fabrication of a feeding obturator are explained to aid in the proper nourishment of neonates for definite corrective procedures in the future with overall growth.